2019
DOI: 10.1080/16549716.2019.1633725
|View full text |Cite
|
Sign up to set email alerts
|

‘I am on treatment since 5 months but I have not received any money’: coverage, delays and implementation challenges of ‘Direct Benefit Transfer’ for tuberculosis patients – a mixed-methods study from South India

Abstract: Background : In March 2018, the Government of India launched a direct benefit transfer (DBT) scheme to provide nutritional support for all tuberculosis (TB) patients in line with END TB strategy. Here, the money (@INR 500 [~8 USD] per month) is deposited electronically into the bank accounts of beneficiaries. To avail the benefit, patients are to be notified in NIKSHAY (web-based notification portal of India’s national TB programme) and provide bank account details. Once these details are entered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 21 publications
3
28
1
Order By: Relevance
“…However, targeting the needy and the poor is essential under these schemes. Previous assessments in India have highlighted several challenges to the implementation of the DBT scheme which needs to be addressed to improve uptake and efficiency ( 21 , 22 ). Also, considering the burden of expenditure due to TB, the amount transferred under DBT would not be enough to provide sufficient compensation for most patients as echoed in other studies ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, targeting the needy and the poor is essential under these schemes. Previous assessments in India have highlighted several challenges to the implementation of the DBT scheme which needs to be addressed to improve uptake and efficiency ( 21 , 22 ). Also, considering the burden of expenditure due to TB, the amount transferred under DBT would not be enough to provide sufficient compensation for most patients as echoed in other studies ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NPY coverage was relatively high at 80%, compared to a previous study from Dakshina Kannada district of Karnataka State, where only 29% of the patients received the money. [ 20 ] This may be due to the differences in study population. While our study included only HIV-infected TB patients, the previous study included all TB patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also alluded to technology related challenges like poor phone and internet connectivity, which are essential for smooth functioning of web-based applications such as Nikshay and PFMS. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…In the case of DBT, the coverage has been low with substantial delays. The limitation of existing tools for DBT poses challenge including the complexity of processes requiring multiple layers of approval and paper-based documentation which overburdened the staff, bulk processing once-a-month, and technological challenges (poor connectivity and issues related to NIKSHAY and PFMS portals) [ 26 ]. Several studies on cash transfers in India in other fields such as food subsidy, pension, etc found that cash transfers suffer from leakages and inaccuracies in beneficiary lists [ 26 ], lags in financial inclusion and biometric identification resulting in absence of bank accounts or Aadhar cards for beneficiaries [ 27 ] or complex and lengthy procedures in linking beneficiary data [ 28 ].…”
Section: Discussionmentioning
confidence: 99%